2018
DOI: 10.1098/rsbl.2018.0570
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for reduced male allocation under selfing in a simultaneously hermaphroditic animal

Abstract: Self-fertilization is widespread among simultaneously hermaphroditic animals and plants, but is often only facultatively deployed under circumstances that constrain outcrossing. A central prediction of sex allocation (SA) theory is that because exclusive selfing reduces sperm or pollen competition to zero, this should favour extreme economy in resources channelled to the male sex function. We can therefore expect that organisms switching from outcrossing to selfing should reduce their male allocation. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Interestingly, an earlier study in M. pusillum —a species that regularly self‐fertilizes—has shown that the species does not exhibit any plasticity in SA in response to group size (Giannakara & Ramm, ). In contrast, M. hystrix —a facultatively self‐fertilizing species—does adjust its SA depending on group size (Winkler & Ramm, ). This suggests that the degree of self‐fertilization could also influence sperm competition and therefore SA and its plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, an earlier study in M. pusillum —a species that regularly self‐fertilizes—has shown that the species does not exhibit any plasticity in SA in response to group size (Giannakara & Ramm, ). In contrast, M. hystrix —a facultatively self‐fertilizing species—does adjust its SA depending on group size (Winkler & Ramm, ). This suggests that the degree of self‐fertilization could also influence sperm competition and therefore SA and its plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…While SA plasticity in response to mating group size is widespread in hermaphroditic animals (reviewed in Schärer, ), the strength and nature of the plasticity vary both among and within species, with some studies showing plasticity only in the male function (Baeza, ; Hoch & Levinton, ; Janicke et al, ; Schärer & Janicke, ; Schärer & Ladurner, ; Winkler & Ramm, ) or the female function (Lorenzi et al, ; Schleicherová et al, ), while other studies show plasticity in either both functions (Janicke & Schärer, , ) or no plasticity at all (Giannakara & Ramm, ). Although a part of this variation in these estimates of plasticity may reflect biases due to the ease with which male and female allocation can be measured in different study systems, it might also reflect different reproductive modes (with different postcopulatory processes, Schärer & Pen, ), species‐specific costs of plasticity (Schleicherová et al, ), or different evolutionary histories (Schleicherová, Sella, & Lorenzi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the generation time is approximately 25 days (Ramm et al 2012). The culture maintained in the laboratory is an inbred line, called SR1 (Zadesenets et al 2016;Winkler and Ramm 2018), which was started in 2011 based on an outbred M. hystrix culture, which initially derived from worms collected in May 2010 from the San Rossore Regional Park (43.684°N…”
Section: Study Organismmentioning
confidence: 99%
“…In Macrostomum, traumatic insemination is called hypodermic insemination, since in several species the donor uses a needle-like stylet (Fig 1) to inject sperm through the epidermis of the mating partner and sperm then move through the body of the recipient to the site of fertilisation [41,57,58]. Injected sperm can often be observed inside the parenchymal tissues of these highly transparent animals [41,[57][58][59], making it feasible to screen a large number of species for the convergent evolution of hypodermic insemination. And while we here present evidence that not all traumatically mating Macrostomum species may inject sperm through the external epidermis, we nevertheless use the term hypodermic insemination for consistency with the earlier literature.…”
Section: Introductionmentioning
confidence: 99%